Mosco convergence of nonlocal to local quadratic forms. (April 2020) - Foghem Gounoue, Guy Fabrice; Kassmann, Moritz; Voigt, Paul
Abstract: We study sequences of nonlocal quadratic forms and function spaces that are related to Markov jump processes in bounded domains with a Lipschitz boundary. Our aim is to show the convergence of these forms to local quadratic forms of gradient type. Under suitable conditions we establish the convergence in the sense of Mosco. Our framework allows bounded and unbounded nonlocal operators to be studied at the same time. Moreover, we prove that smooth functions with compact support are dense in the nonlocal function spaces under consideration.